PERSEPSI PASIEN DARI KUALITAS LAYANAN DAN LAYANAN YANG DIINGINKAN (GAP ANALYSIS) : STUDI PERBANDINGAN PADA RUMAH SAKIT UMUM PKU MUHAMMADIYAH DI BANTUL DAN YOGYAKARTA - Supripto, Supripto (Universitas Muhammadiyah Magelang, 2006)
This study examine about research atudy to compare service aualities in service company on hospitals, i.e., PKU Muhammadiyah Bantul hospital and PKU Muhmmadiyah Yogyakarta hospitals. The first research study, examine gap analysis (gap difference) between patient perception about PKU Muhmmadiyah Bantul and Yogyakarta hospital service, with hospital expectation service. The second research study, examine difference service qualities and service value on PKU Muhammadiyah Bantul and Yogyakarta hospitals. Research data collected from responden as direct in patient PKU Muhammadiyah Bantul and Yogyakarta. Test using in this research is paired sample t test (uji sampel berpasangan). The gap analysis studi about service perseption and expectation service with compare study found patient perception about service quality on PKU Muhammadiyah Bantul hospitals is not same with patient expectation on hospitals. Patient perception about service quality on PKU Muhamadiyah Yogyakarta hospitals is not same with patient expectation on hospitals. About the quality rank and value rank, service quality rank on PKU Muhammadiyah Bantul hospitals majority is good and quality value rank is very good. Service quality rank on PKU Muhammadiyah Yogyakarta hospitals majority is good and quality value rank is good. This research hoped give academist contribution for researchs about quality inthe next time.